The Modern Approaches and Future Perspectives on Breast and Ovarian Cancer Prevention Strategies in BRCA1 and BRCA2 Mutation Carriers: A Literature Overview - Sandra Sarnacka; Jakub Kordialik; Julia Koćwin; Paula Bieganek; Bartosz Sadłowski; Stanisław Łukaszewicz; Piotr Pawłowski; Julia Rybak; Michał Tokarski; Angelika Banasiak (Kazimierz Wielki University, 2024)
Individuals with BRCA1 and BRCA2 mutations face significantly heightened likelihood of developing breast and ovarian cancers.  Besides some lifestyle recommendations, like maintaining physical activity, healthy BMI, possibly early parenthood and breastfeeding, the management of BRCA1/2 mutation carriers includes gene mutation early-detection, screening, risk-reducing surgeries, and chemoprevention. Various prevention strategies exist, all aimed at monitoring patients and mitigating the cancer risks. However, even with the existence of national and international guidelines to direct prevention efforts, there is no ideal protocol that would be universally applicable for all individuals with mutated BRCA gene. This article aims to delve into the currently available surveillance and preventive strategies and explore the potential future avenues for early detection and risk reduction in BRCA mutation carriers.